MODEL PEMBELAJARAN IPA BERBASIS DIGITAL LITERASI SEBAGAI UPAYA KONSTRUKTIVISME KARAKTER SISWA KEPADA MASYARAKAT DI SMK NEGERI 3 PEMATANGSIANTAR - Srinatalia Silaen; Hani Jesika Purba; Desi Ester Idawati Sitohang; Putri Siregar (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
The development of information and commuincation technology (ITC) has influenced almost all aspects of life, including the world of education,. At SMK Negeri 3 Pematangsiantar, the implementation of a digital literacy-based science learningg model is expected to shape the character of student who are not only skilled in the field of natural sciences (IPA) but alsohave critical, creative, and responsible thingking skills. This study aims to explore the implementation of a digital literacy-based science learning model and its impact on students character constructivism. The research method used is a qualitative approach with case studies. Data collection techniques are carried out through interviews, observations, and documentation. The results of the study indicate that the implementation of this learning model has succeeded in improving students understanding of science concepsts and facilitating the formation of student character, such as creativity, independence, and social responsibility. Digital literacy-based learning also has a positive impact in society through students active participation in various social and scientific activities. Therefore, this model can be one of the efforts in creating a generation that is ready to face the challenges of an incresingly comlex world.